Biomimetic Pyramid Structure Film for Enhancing Building Radiative Cooling - Qian‐Hao Pan; Mei‐Hua Wang; Zong‐Ying Huang; Xiao‐Jing Qiu; Yu‐Tao Wang; Fu‐Xing Zhao; Meng‐Han Zhu; Xin Guo; Chen Chen; Si‐Chao Zhang; Jin‐Long Wang; Zhen He; et al. (Advanced Science)
Abstract Radiative cooling has emerged as a promising technique for reducing energy consumption in building thermal management due to its passive cooling property and no external energy requirement. Despite significant advances, scalable production of artificial photonic radiators with periodic structures, environmental stability, high radiative cooling performance, and economic applicability is still challenging in most state‐of‐the‐art radiative coolers. Rational structure and materials design are essential to promote daytime sunlight reflectance while maintaining a high emissivity within the atmospheric window (8–13 µm). In this work, inspired from the unique hair structure of heat‐resistant organisms, a biomimetic micro‐pyramid shaped structure model is analyzed. By mimicking the intricate design with a silicon template, a radiative cooling film containing specialized micro‐pyramid structure is fabricated by integrating high dielectric constant materials with polymers and receiving PVDF coating. The resulting film boasts a solar reflectance of 97.3% and an exceeding 98% infrared light emission within the atmospheric window. In addition, silicon rubber endows this membrane with strong tensile and rebound properties while surficial hydrophobicity protects the membrane from dust infestation. Considering the manufacturing simplicity and cost‐effectiveness, this method shows great potential for mass production, shedding light on building thermal management.